How serious are health impacts in one of the most polluted regions of Central Europe? - Jiřík, Vítězslav; Dalecká, Andrea; Vašendová, Veronika; Janoutová, Jana; Janout, Vladimír (Reviews on environmental health, 2017)
BACKGROUND: The long-term exposure to pollutants in ambient air is associated with higher mortality and occurrence of respiratory and cardiopulmonary diseases. The longitudinal cross-section study focuses on the associations between long-term exposures to carcinogenic and non-carcinogenic pollutants and the prevalence and incidence of such specific diseases including immunodeficiencies. METHODS: The data on health status from industrial and non-industrial regions were obtained from health documentation for a 5-year period from 2007 to 2011 and represent the whole population living in polluted (1,249,323 inhabitants) and unpolluted (631,387 inhabitants) regions. The data on concentrations of PM10, PM2,5, NO2, SO2, benzene and benzo[a]pyrene were collected. The concentrations of pollutants were estimated from measured data by using dispersion models. The average population-weighted concentration of pollutants, which is representative for a defined geographic area and time period from 2007 to 2011, was calculated from the obtained data. The logistic regression and the Mantel-Haenszel χ2 test were used to determine the odds ratios (OR) and p-values for a linear trend. Moreover, the relative risks of mortality and morbidity to specific diseases were calculated according to theoretical dose-response association published by World Health Organization (WHO). RESULTS: The probability of incidence of chronic obstructive pulmonary disease and bronchial asthma is statistically significantly higher in the population living in the polluted region compared to the population living in the unpolluted region. The association between long-term exposure to pollutants and the prevalence of immunodeficiency with predominantly antibody defects (D80) was confirmed. The strongest association was found for exposures to particulate matter (PM2,5). The prevalence of immunodeficiency with predominantly antibody defects was also observed in both regions depending on the age of the population and statistically significant difference was only found in the group of adults (20 and over). CONCLUSION: These associations encourage the hypothesis, that the long-term exposure to PM2.5 might cause the activation of cellular immune response. Further research is needed to explore the correlative immunoregulatory mechanism linking PM2.5 (or other pollutants - SO2) and immune cells. Nowadays, it is also believed that these associations are important in the increase of incidence of immune inflammatory response which is proven risk factor for cardiovascular disease (atherosclerotic disease, coronary heart disease and sudden cardiac death). Positive association between long-term exposure and prevalence of bronchial asthma and chronic obstructive pulmonary disease might be skewed due to important socio-economic factors (especially smoking).
Keywords: Prevalence; monitorování životního prostředí; průřezové studie; longitudinální studie; znečištění ovzduší; lidé; Air Pollution; Carcinogens; Incidence; prevalence; Cross-Sectional Studies; incidence; karcinogeny; Air Pollutants; Cardiovascular Diseases; Czech Republic; Environmental Monitoring; kardiovaskulární nemoci; vystavení vlivu životního prostředí; Česká republika; látky znečišťující vzduch; Environmental Exposure; Longitudinal Studies; Humans